Masalah dalam pelaksanaan pembelajaran koperatif satu persepsi guru - Naimah, Ibrahim (2009)
The aim of this research was to survey the problems of Cooperative Learning implementation among Secondary School teachers in Kota Setar District. This research had involved 200 teachers, who are teaching different subjects. The questionnaire was used to test the teacher's knowledge and skills in the implementation of Cooperative Learning. The data was collected to identify the major problems in the implementation of Cooperative Learning. Descriptive Statistic, t-Test, ANOVA and Pearson Correlation were used to analyzed this data. This research had proved that the main aspect which teachers face problems in the implementation of Cooperative Learning was skill aspect, the majority teachers were not well prepared with their structured teaching materials. There were four more problems which were at the average level, teachers were difficult to evaluate the students through their group work, students did not do their group assignment co-operatively, teachers were unable to control their classes when student made noise and the infrastructure in the classroom had caused obstruction on Cooperative Learning implementation. Furthermore, there was significant difference between the assignment done by the students given by the male and female teachers. There was also significant difference between teachers unable to control their classes when student made noise and obstruction of the infrastructure inside the classroom may had caused by their training period. Anyway, age, teaching experience and subjects did not caused significant difference in this problems. However the research had shown that there was no significant relationship between the problems on Cooperative Learning implementation and the supports given to the teachers and how they got their skills